Impact of Age, Gender, and Body Composition on Balance, Coordination, and Agility in Children and Adolescents - Ebrahimi, Mohsen; Changizi, Mehdi (International Journal of Sport Studies for Health, 2025)
Objective: Balance and coordination are crucial for the development of motor skills and are influenced by age and gender. This study aimed to examine the effects of age and gender on balance, coordination, and agility in children and adolescents. Methods and Materials: A total of 405 participants (211 boys and 194 girls) aged 7 to 13 years were assessed. Static balance (with eyes open and closed) was measured with the Stork Test, coordination was assessed using the Eye-hand coordination test, and agility was measured through the T-test and 4×9 test. Pearson correlation and independent t-test were used for data analysis. Findings: The results indicated significant differences in BMI (Р=0.048) and body fat percentage (Р=0.001) in girls compared to boys at age 9, as well as in static balance with eyes closed at ages 7 (Р=0.034) and 10 (Р=0.003). Coordination was also significantly higher in boys than girls at ages 11 (Р=0.000) and 12 (Р=0.000). Furthermore, body fat percentage was found to have a stronger effect on balance and motor function in boys than in girls. Conclusion: Based on these findings, maintaining a healthy body fat percentage is recommended for both genders to support better health and physical performance.